The Circular RNA-miRNA Axis: A Special RNA Signature Regulatory Transcriptome as a Potential Biomarker for OSCC - Ramanathan Saikishore; Palanivel Velmurugan; Dhandapani Ranjithkumar; Ragunathan Latha; Thangavelu Sathiamoorthi; Ashokbabu Arun; Arumugam Veera Ravi; Subpiramaniyam Sivakumar (Elsevier, 2020)
Oral squamous cell carcinoma (OSCC) is a highly recurrent form of cancer arising from the oral epithelium, which is the result of mutational change due to etiological factors such as tobacco, smoking, chewing of areca nuts, and alcohol consumption. OSCC occurrence has been observed to be prevalent in different regions of Pacific countries and in most Asian countries. Despite the accessibility of the oral cavity, OSCC is diagnosed at an extremely late stage of pathogenic tumor node metastasis pTNM (III-IV), resulting in a poor prognosis for the individual. Therefore, it is important to make definitive, early, and efficient diagnoses. Owing to the development of omic-natured studies, the presence of proteins, transcribed elements, metabolic products, and even microflora detected in saliva helps us to select biomarkers, which is an especially exciting potential because of the availability and the non-invasive nature of sample collection. Since the discovery of circular RNA (circRNA) by Sanger sequencing, it has been reported to play a pivotal role in several human diseases, including cancer. circRNA functions as a microRNA (miRNA) sponge in the regulation of mRNA expression, forming the circRNA-miRNA regulatory axis. In the case of OSCC, overexpression of different circRNAs exhibits both tumor-progressive and tumor-suppressive effects.